2017
DOI: 10.1111/1753-6405.12594
|View full text |Cite
|
Sign up to set email alerts
|

The association between exposure to interpersonal violence and suicide among women: a systematic review

Abstract: Although the association between suicide and interpersonal violence requires further investigation, being a victim or perpetrator of violence appears to be associated with risk of suicide. Future research should focus on the impact that the type of violence, victim-perpetrator relationship and proximity of violence has on the risk of death from suicide. Implications for Public Health: There may be significant opportunity for targeted suicide prevention strategies among women who have been victims or perpetrato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 80 publications
(323 reference statements)
2
21
0
Order By: Relevance
“…For example, in analyses of the mid-aged women in the Australian Longitudinal Study on Women’s Health (ALSWH), Loxton, Schofield, and Hussain found strong and consistent relationships among domestic violence, poorer mental health, and depression [ 12 ]. In addition, results of a recent meta-analysis conducted by MacIsaac and colleagues showed a strong association between interpersonal violence and suicide among women [ 13 ]. Compared to their heterosexual counterparts, sexual minority women are at increased risk for mental health problems such as depression, anxiety disorders, and substance abuse [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in analyses of the mid-aged women in the Australian Longitudinal Study on Women’s Health (ALSWH), Loxton, Schofield, and Hussain found strong and consistent relationships among domestic violence, poorer mental health, and depression [ 12 ]. In addition, results of a recent meta-analysis conducted by MacIsaac and colleagues showed a strong association between interpersonal violence and suicide among women [ 13 ]. Compared to their heterosexual counterparts, sexual minority women are at increased risk for mental health problems such as depression, anxiety disorders, and substance abuse [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that 42% of women who had experienced intimate partner violence reported suicidal ideation and 31% reported having attempted suicide at some point in their life ( 37 ) . A recent systematic review also pointed out that women who were exposed to intimate partner violence may be at high risk of death from suicide ( 38 ) .…”
Section: Discussionmentioning
confidence: 99%
“…as childhood abuse or intimate partner violence), 20,21 which is associated with increased risk for suicide. 22 This is particularly concerning for those living in rural communities, where intimate partner violence tends to be more severe, chronic, and is associated with worse health and psychosocial outcomes, 23 compared to urban settings. Unfortunately, resources for addressing interpersonal violence in rural communities are more limited, with more barriers to help-seeking (eg, confidentiality concerns, local politics, distance), greater areas of need for specific services, 24 and cultural norms that can deter disclosure and help-seeking.…”
Section: Interpersonal Factorsmentioning
confidence: 99%